A needs assessment evaluation of information technology student mobile website design skills - Oraboot Wuttikamonchai; Paitoon Pimdee; Jaruwan Ployduangrat; Aukkapong Sukkamart (My University, 2024)
In this study, we present a comprehensive needs assessment (NA) aimed at identifying key factors that contribute to enhancing instructor skills in mobile website design (MWDS). In the realm of professional development, the significance of NAs for user experience (UX) designers has gained attention, with scholars emphasizing the importance of competency modeling to elucidate the intricate knowledge, skills, and abilities inherent in UX design. This perspective aligns with the essential nature of learning NAs for continuous professional development. Therefore, the objective of our investigation was to evaluate the current state of instructor MWDS and their real-world user experience through a sample of 41 individuals, including information technology (IT) instructors and IT entrepreneurs. Employing a simple random sampling method in August 2023, our study utilized descriptive statistics to analyze the data, revealing a moderate proficiency level (mean [M]=3.40). Interestingly, the highest rankings in our findings were attributed to planning mobile website design from a user experience perspective (M=3.81) and developing or creating a website for mobile devices user experience (M=3.81). These skills demonstrated consistent high perceived importance (M=4.78). Moreover, specific aspects of MWDS stood out in terms of significance, with developing or creating mobile websites’ user experience holding the top priority (M=4.87), followed closely by designing mobile websites’ user experience (M=4.79) and developing or prototyping mobile websites’ user experience (M=4.77). Our findings underscore the urgent need to prioritize the promotion of MWDS, particularly those focused on user experience. Using priority needs index modified (PNImodified) method, we identified that user research holds the highest priority (PNImodified=0.56), followed closely by mobile website design user experience (PNImodified=0.41), and defining website content for mobile devices user experience (PNImodified=0.40). This information provides valuable insights for educational institutions and industry stakeholders, guiding efforts to enhance instructor skills and align curricula with the evolving demands of mobile web design. In summary, our study sheds light on the current state of instructor MWDS, emphasizing the importance of user experience-related competencies. The identified priority needs offer valuable guidance for educational institutions and industry stakeholders, facilitating efforts to enhance instructor skills and align curricula with the dynamic requirements of mobile web design. Notably, our results align with the hypothesis testing, where paired sample t-test statistics found that both overall and individual aspects indicated a statistically significant preference for desired over actual outcomes at the .01 level.
Keywords: Electronic learning; Mobile Learning in Education